The clinical effect and safety of non-pharmacological Chinese medicine therapy in treating chronic nonspecific low back pain: a systematic review and network meta-analysis protocol - Cui, Shifang; Liu, Lin; Zhang, Fuli (Frontiers in Pharmacology, 2025)
IntroductionChronic nonspecific low back pain (CNLBP) significantly affects individual wellbeing, compromising physical health, quality of life, and productivity. As healthcare approaches expand, Non-pharmacological Chinese Medicine Therapies (NPCMT) have garnered global interest. This systematic review and network meta-analysis (NMA) aims to rigorously evaluate the effectiveness and prioritization of various NPCMT interventions for CNLBP, including acupuncture, tui na, gua sha, cupping therapy, taijiquan, baduanjin, yijinjing, and qigong, ultimately providing evidence-based recommendations for healthcare professionals.Methods and AnalysisOur strategy encompasses a meticulous hunt for randomized controlled trials (RCTs) that evaluate Non-pharmacological Chinese Medicine Therapies for treating chronic nonspecific low back pain. This exploration will span an array of databases, such as Web of Science, Cochrane Library, EMBASE, PubMed, China National Knowledge Infrastructure, China Science and Technology Journal Database, Wanfang Database, China Biology Medicine disc, and ClinicalTrials.gov. Our examination will be comprehensive, encompassing evaluations of risk of bias, meta-analytic procedures, analyses of subgroups and sensitivity, assessments concerning publication bias, and the determination of the quality of evidence.ConclusionThis study aims to offer valuable insights into the safety and efficacy of various Non-pharmacological Chinese Medicine therapies for patients with CNLBP. It is hoped that these findings will guide future clinical practice and research in identifying the most suitable treatment methods for CNLBP patients.